Manifest Sādātových vrahů: analýza a kontext - Kořínek, Jan (Sacra, 2018)
Al-Farīda al-Ghā'iba ('Neglected Duty') captures views of a group of militant activists who called themselves the Jihad Organization (arab. Džamā'at al-džihād). They were responsible for the assassination of Egyptian president Anwār Sādāt in 1981. The author of the text, Muhammad 'Abd as-Salām Farāj (d. 1982), is attempted to legitimize the views and actions of the group using citations from the Quran and Sunna (tradition) as well as using the texts of influential religious authorities. One of the objectives of this paper is to show how Farāj used these texts. Farāj grew up in a very turbulent time following the revolution of 1952. For analysis of the views captured in his text it is necessary to outline the socio-political context of this time. The paper attempts to show Farāj's text and the views portrayed in it as an important intermediary between the ideology of the Muslim Brotherhood and groups which follow the model of the Jihad Organization in placing major emphasis on the establishment of an Islamic state through militant actions.